From laughter to awareness: Illocutionary acts in English environmental memes - Nurul Aini; Siti Amsariah; Eny Maulita Purnama Sari; Luthfiana Dwi Rakhmawati; Ariyani Etik Kurniasari (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2026)
This research analyzes kinds and communicative functions of speech acts in amusing English-language memes about environmental awareness to support Sustainable, Development, Goals (SDGs) 13 Climate Action. Referring to Speech Act Theory, this study explores how humor functions as a pragmatic strategy to promote ecological messages in digital domains. The data was purposively collected from English-language memes on Instagram and Facebook from 2023 to 2025. Every meme was analyzed using pragmatic content analysis to determine illocutionary acts and identify their role in forming ecological discourse. Findings showed that assertive, directive, and expressive acts prevailed in the dataset, representing an effort to educate, criticize the state world, and encourage audiences to take sustainable actions. Expressive acts were the most dominant, using sarcasm and irony to express frustration and humor regarding environmental degradation. Multimodal nature of memes indicates that illocutionary force is co-constructed through text, image, typography, and visual composition, whereby pragmatic meaning arises from the whole semiotic design rather than the words alone. This study broadens the understanding of digital humor by framing memes as performative tools of environmental advocacy, not merely as entertainment. It also contradicts previous studies suggesting that assertive actions are commonly found in English-language memes.